Perspektif Pendidikan Anak Menurut Syaikh Muhammad Syakir dan Relavansinya dalam Pendidikan Islam Modern di Era Society 5.0 - Mardliyah, Aina'ul (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2024)
Education is utilized as a platform to cultivate critical thinking abilities, with the application of technology that impacts religious, national, and governmental aspects of life. This research analyzes the concept of child education, focusing on the perspective of Syaikh Muhammad Syakir and its relevance to modern Islamic education in the era of Society 5.0. Research method: literature review, specifically library research with descriptive analysis. Research findings: (1) The perspective of Syaikh Muhammad Syakir in his work